Integration and Applications of Linear Algebra in STEM Programmes: A Case Study of Ghanaian Universities - Clement Ayarebilla Ali; Eric Kwasi Avivor (Universitas Negeri Surabaya, 2026)
Linear algebra serves as a critical tool in propelling Science, Technology, Engineering, and Mathematics. So, this study aims to explore the level of integration into university curricula, its applications, and challenges. The study adopts the systems theory and linear system theory frameworks to provide a structural and analytical perspective on the integration and application. A cross-sectional research design was employed to gather data from two University undergraduate students pursuing the domain in Ghana. The findings revealed the disparity between theoretical instruction and practical application, as 41.3% affirmed the perception, emphasizing the need for curriculum reforms, increased use of computational tools, and interdisciplinary collaborations. It was therefore recommended that stakeholders strive to improve pedagogical strategies, strengthen industry collaboration, and invest in modern technology tools to enhance the application of linear algebra education.